واقع التسرب المدرسي بالمدارس الجزائرية (دراسة ميدانية بثانوية عبد المجيد بومادة بمدينة ورقلة) - بن عم, نور الهدى (Changement Social, 2019)
التربية والتعليم شعار تنادي به شعوب العالم قصد الحد من شبه الأمية والجهل من أجل التحضر والتطور والتقدم التكنولوجي والتقني، خاصة والعالم يشهد في السنوات الأخيرة منعرجا أخر في إطار سياسة العولمة، والسياسة الأساسية المتبعة لتحقيق ذلك هي تكوين وتعليم الفرد قصد التحكم في مختلف اللغات من أجل نزع الحواجز وتواصل مختلف الحضارات والثقافات إلا أن التعليم يعرف عدة مشاكل وعراقيل تحول دون الوصول بالفرد إلى المبتغى، وتبدأ المشكلات من خارج المؤسسة التربوية حيث المجتمع والأسرة وتتجسد داخل المؤسسة حيث التعليم،ومن بين هذه المشكلات وأخطرها التسرب المدرسي الذي سنتناوله في هذه الدراسة  التي تهدف الى معرفة معاني و دلالات هذا المتغير و أسباب التسرب المدرسي لدى تلاميذ الطور الثانوي و الفروق بين الجنسين. الكلمات المفتاحية: التسرب المدرسي/ العوامل النفسية/ العوامل الاجتماعية/ العوامل التحصيلية/ المراهقة. Education is a slogan advocated by the peoples of the world in order to reduce illiteracy and illiteracy for urbanization, development and technological and technical progress, In particular, the world has witnessed a new development in recent years, the basic policy to achieve this is the formation and education of the individual in order to control the various languages in order remove barriers and continue to different civilizations and cultures, but education knows several problems and obstacles to individual access to his intended, and start problems from outside the educational institution where the society and the family is embodied within the institution where education, and among these problems, the most serious of the school the dropout taken up in this study, which aims to find out the meanings and connotations of this variable and the reasons for dropping out of school at the secondary stage pupils and gender differences. Keywords: school dropout/ psychological factors/ social factors/ achievement/ adolescence factors